Arrival Directions of Cosmic Rays above 32 EeV from Phase One of the Pierre Auger Observatory - Abreu, P.; Aglietta, M.; Albury, J.M.; Allekotte, Ingomar; Mollerach, Maria Silvia; Almeida Cheminant, K.; Zapparrata, O.; Zas, E.; Zavrtanik, D.; Zavrtanik, M.; Zehrer, L. (IOP Publishing, 2022)
Fil: Abreu, P.. Instituto Superior Tecnico; Portugal. Universidade Nova de Lisboa; Portugal